FILSAFAT ILMU AKUNTANSI SEBUAH TINJAUAN PADA ASPEK EPISTEMOLOGIS ISLAM - Naini, Yusnaini (Balance : Jurnal Akuntansi dan Bisnis, 2016)
Conventional accounting is now developing is a product of the capitalist environment, the information it contains disampaikannyapun capitalist values. The phenomenon of the failure of conventional accounting to meet people's demands for financial information is correct and fair, raise awareness among Muslim intellectuals will need accounting knowledge Islami. Reformulation of the conceptual framework of financial reporting by basing on the principles of truth, honesty and justice becomes very urgent to do. Islam delivered the Prophet Muhammad covers the entire universe which of course include all mankind. This is where the differences between conventional accounting familiar with sharia accounting. Existence of accounting in Islam can be seen from a variety of historical evidence and of the Holy Qur'an. In Surat Al-Baqarah verse 282, discussed issues muamalah. Thus the epistemological aspect of reviews on conventional accounting knowledge is not based on the nature of science that comes from God is revealed through revelation